PERANCANGAN PEMESANAN AIR GALON BERBASIS WEB - Martan, Martan Gelisa Halawa; Sitohang, Sunarsan (Computer Science and Industrial Engineering, 2022)
Most of human body is made up of fluids. Water is used for various tihings such as for washing, bathing, and drinking water. So with that, many people have opened drinking water business by opening refill drinking water depots. As technology is quite rapidly developing, this situation makes people try new ways to utilize tecnology to make it easier to develop their business. The problem of this research is that the number of refill drinking water depot businesses compotition tighter. Where the company seeks to find as many customers as possible. Putra Jaya drinking water depot, where many people still don’t know about Putra Jaya drinking water depot. This leaves less company opinion. A refill drinking water depot must maintain the image of the company and maintai consumer confidence so that consumers always buy at the company. Researchers conclude to advance research gallon refill water depot business. Researchers use the prototyping method in web application development. Using a visual studio code application with laravel, php, mysql database to develop the Putra Jaya drinking water depot business. Buyers of gallon water refill via the website and don’t bother coming to the location.